Effects of LL-37 on Gingival Fibroblasts: A Role in Periodontal Tissue Remodeling? - Maelíosa T. C. McCrudden; Katherine O’Donnell; Chris R. Irwin; Fionnuala T. Lundy (Vaccines, 2018)
Mounting evidence suggests that the host defence peptide, LL-37, plays a role in both inflammation and in wound healing; however, the role of this peptide in the remodeling and maintenance of oral tissues is not yet fully understood. Fibroblasts are the most abundant cell type within the periodontal tissues, and gingival fibroblasts play an important role in maintaining and repairing the gingival tissues which are constantly exposed to external insults. In this study we examined the direct effects of LL-37 treatment on gingival fibroblasts and found that LL-37 significantly increased secretion of both interleukin 8 (IL-8) and IL-6 from these cells. LL-37 tended to decrease matrix metalloproteinase (MMP) activity in gingival fibroblasts, but this decrease did not reach statistical significance. LL-37 significantly increased tissue inhibitor of metalloproteinase-1 (TIMP-1) production by gingival fibroblasts, but had no significant effect on TIMP-2 levels. LL-37 was also shown to significantly increase production of basic fibroblast growth factor (bFGF), hepatocyte growth factor (HGF), and keratinocyte growth factor (KGF) in gingival fibroblasts. Taken together, these results suggest an important role for the host defence peptide, LL-37, in modulating the fibroblast response to remodeling in periodontal tissues.